A Desain Karakter Board Game Pengenalan Fauna Bagi Anak SLow Learner - Andika Perdana Putra; Masnuna; Widyasari (Jurusan Pendidikan Luar Biasa, 2026)
Education for slow learners requires special strategies due to intellectual and emotional barriers, such as anxiety and low self-confidence, which hinder the process of information digestion. This study aims to design character designs in the board game